DIFFERENTIATION THROUGH THE EXPERIENCE: DIÁRIO CATARINENSE'S CASE - DIFERENCIAÇÃO ATRAVÉS DA EXPERIÊNCIA: O CASO DO DIÁRIO CATARINENSE (Gestão & Regionalidade, 2009)
Strategic positioning must be established throughdifferentiation. And it may be configured acrossexperience movements. For its turn, experiences aregetting increasingly plentiful in their own right as aproduct offering and in conjunction with productsand services as a way to provide additional value toconsumers. But the creation of experiences mustbe the way to create new economic value for thecompany, which performs those experiences. Thispaper seeks to broad the comprehension ofexperiences as differentiation of strategy, and usea case study originated from a Brazilian newspaperthat started to add experience events into itssections. The result shows how a media companymay use this tool in order to differ itself and createvalue. It means that the creation of value andprofitable growth through the experience may bethe emerging opportunity space for mediacompanies that may transform its entertainmentproducts (programs, newspapers, magazines) inexperimental products.Keywords: Differentiation, Experience, Strategicpositioning